Effect of the addition of Y and Y2O3 on microstructure and mechanical properties of 15Cr-15Ni ODS steel. (June 2022) - Zhao, Ruilin; Jia, Haodong; Cao, Shuguang; Tong, Zhenfeng; Zhou, Zhangjian
Highlights: 15Cr-15Ni ODS steels with the addition of Y and Y2 O3 respectively have been prepared. The distribution of particles in 15Cr-15Ni-Y is more homogeneous than that of 15Cr-15Ni-Y2 O3 . 15Cr-15Ni-Y shows better high temperature plasticity than 15Cr-15Ni-Y2 O3 . Abstract: 15Cr-15Ni ODS steels with the addition of Y or Y2 O3 were fabricated via the mechanical alloying and hot isostatic pressing, followed by forging treatment (named as 15Cr-15Ni-Y and 15Cr-15Ni-Y2 O3, respectively). The morphology of as-milled powders of 15Cr-15Ni-Y was flatter than that of 15Cr-15Ni-Y2 O3 . As-forged samples were characterized by high-resolution transmission electron microscope. The oxide particles in both 15Cr-15Ni-Y and 15Cr-15Ni-Y2 O3 ODS steels were identified as δ-Y4 Zr3 O12 . The mean size and number density of dispersed nanoparticles in 15Cr-15Ni-Y and 15Cr-15Ni-Y2 O3 ODS steels were 13.6 nm, 2.5 × 10 22 /m 3 and 12.8 nm, 5.5 × 10 22 /m 3, respectively. The tensile test at room temperature and 700℃ indicated that the tensile strength of 15Cr-15Ni-Y was lower than that of 15Cr-15Ni-Y2 O3 ODS steel, while the total elongation of 15Cr-15Ni-Y was higher. The theoretical value based on the strengthening mechanism was calculated and discussed as well.